A hexadecanuclear silver alkynyl cluster based NbO framework with triple emissions from the visible to near-infrared II region. Issue 84 (4th October 2018) - Zhang, Shan-Shan; Su, Hai-Feng; Zhuang, Gui-Lin; Wang, Xing-Po; Tung, Chen-Ho; Sun, Di; Zheng, Lan-Sun
Abstract : A hexadecanuclear silver alkynyl cluster based NbO framework with triple emissions from visible to near-infrared II region. Abstract : Compared to emissive silver-thiolate clusters, their alkynyl cousins are, however, usually luminescence silent. Herein we report a novel silver-alkynyl cluster based NbO-type framework (SD/Ag18 ) showing unprecedented triple emission spanning from the visible to near-infrared (NIR) region. It is a 3D framework constructed from a [Cl@Ag16 ] cluster based unit, which is further quadruply bridged by the surrounding four Ag atoms through Ag⋯Ag interactions, giving a 4-connected NbO topology. AlthoughSD/Ag18 exhibits weak orange-red emission at room temperature, its emission becomes strong upon cooling, with three emission maxima at 524, 647 and 1036 nm, respectively, covering both the visible and NIR regions. The visible emissions involve triplet alkynyl-to-metal charge transfer mixed with a cluster-centered state, whereas the participation of cPrCC − in the frontier orbitals of the cluster may be responsible for the NIR emission. The unusual emissions, especially in the NIR-II region, are observed, for the first time, in silver complexes.